The Impact of Detector Placement on Signalized Intersection Performance - Koltovska Nečoska, Daniela; M. Bombol, Kristi (Promet - Traffic&Transportation, 2012)
Despite the flow fluctuations and increased traffic demand in the Macedonian cities over the last fifteen years, the Republic of Macedonia is one of those countries which still employ only the traditional systems of traffic management and control. Those are fixed control systems that certainly cause problems such as increased travel times and travel expenses as well as environmental degradation. A general call for “…something has to be done…” becomes obvious. The best practices have shown that this can be realized through unconventional solutions i.e. by means of responsive traffic management. A very reasonable example of such a system is the vehicle actuated control system that we have found to be quite challenging to do our research. Thus, we set up two folded research issues in front of us. The first one was to scientifically prove that vehicle actuated signal control can really be a reasonable substitute for a fixed time signal control, which will enhance the overall signalized intersection performance provided the timing parameters and the detector placement ŕrĺ properly designed. The second one was to indicate that such an advanced control system is feasible and sustainable for Macedonian cities. This paper focuses on the first research issue only. For this purpose, a semi-actuated signal control strategy on an appropriately chosen signalized intersection was designed. The primary objective was to determine the way in which the inductive loop detector placement from the STOP line affects the overall intersection performance. To meet the goal, two scenarios were designed: 1. Detector placement at the STOP line, and 2. Detector placement at 8 metres behind the STOP line. Emphasis was placed on the semi-actuated signal control algorithm design. The designed algorithm was then applied in the net of VISSIM in order to simulate the semi-actuated signal control process. Performance comparison analysis with the formerly pre-timed signal control strategy followed. It was concluded that the overall intersection performance could be improved both by adequate inductive loop detector placement and by interaction with signal parameters. Hence, the placement distances would have to be considered under the limitation conditions only. KEYWORDS: signalized intersection, vehicle actuated control, semi-actuated control, inductive loop detectors, simulation, delays, level of service